DISSECTING OCD CIRCUITS: FROM ANIMAL MODELS TO TARGETED TREATMENTS. Issue 8 (7th May 2015) - Ahmari, Susanne E.; Dougherty, Darin D.
<x xml:space="preserve">Abstract</x> Obsessive–compulsive disorder (OCD) is a chronic, severe mental illness with up to 2–3% prevalence worldwide. In fact, OCD has been classified as one of the world's 10 leading causes of illness‐related disability according to the World Health Organization, largely because of the chronic nature of disabling symptoms.[1] Despite the severity and high prevalence of this chronic and disabling disorder, there is still relatively limited understanding of its pathophysiology. However, this is now rapidly changing due to development of powerful technologies that can be used to dissect the neural circuits underlying pathologic behaviors. In this article, we describe recent technical advances that have allowed neuroscientists to start identifying the circuits underlying complex repetitive behaviors using animal model systems. In addition, we review current surgical and stimulation‐based treatments for OCD that target circuit dysfunction. Finally, we discuss how findings from animal models may be applied in the clinical arena to help inform and refine targeted brain stimulation‐based treatment approaches.